Sec22 regulates endoplasmic reticulum morphology but not autophagy and is required for eye development in Drosophila. - Zhao, X.; Yang, H.; Liu, W.; Duan, X.; Shang, W.; Xia, D.; Tong, C. (Journal of Biological Chemistry, 2015)
The endoplasmic reticulum (ER) is a highly dynamic organelle that plays a critical role in many cellular processes. Abnormal ER morphology is associated with some human diseases, although little is known regarding how ER morphology is regulated. Using a forward genetic screen to identify genes that regulated ER morphology in Drosophila, we identified a mutant of Sec22, the orthologs of which in yeast, plants, and humans are required for ER to Golgi trafficking. However, the physiological function of Sec22 has not been previously investigated in animal development. A loss of Sec22 resulted in ER proliferation and expansion, enlargement of late endosomes, and abnormal Golgi morphology in mutant larvae fat body cells. However, starvation-induced autophagy was not affected by a loss of Sec22. Mosaic analysis of the eye revealed that Sec22 was required for photoreceptor morphogenesis. In Sec22 mutant photoreceptor cells, the ER was highly expanded and gradually lost normal morphology with aging. The rhabdomeres in mutants were small and sometimes fused with each other. The morphology of Sec22 mutant eyes resembled the eye morphology of flies with overexpressed eyc (eyes closed). eyc encodes for a Drosophila p47 protein that is required for membrane fusion. A loss of Syntaxin5 (Syx5), encoding for a t-SNARE on Golgi, also phenocopied the Sec22 mutant. Sec22 formed complexes with Syx5 and Eyc. Thus, we propose that appropriate trafficking between the ER and Golgi is required for maintaining ER morphology and for Drosophila eye morphogenesis.